WHICH PSYCHOLOGICAL FEATURES DO COLLEGE STUDENTS VALUE IN THEIR PROFESSORS? - Casillas Martín, Sonia (2016)
For more than three decades, teaching work assessment based on the student’s perception has been used. This is considered one of the most classical and most used models within institutions. This paper seeks to identify the concept of a good college professor according to the psychological features valued by students. To this end, a longitudinal, quantitative study was conducted on a sample of more than 6000 students, in a repeated manner, over a 10-year time period. The tool used for gathering data was a questionnaire composed of an adjective scale with a Likert-type option. It underwent a pilot study and was evaluated by experts as validation procedures. The results obtained identify the psychological traits proposed by students to define a good professor. These are related to basic personal traits, personal values, as well as to sociability and participation, psycho-sociological aspects and interpersonal relationship aspects.